A synthesis of tiruchanduramine and a reinvestigation of its glycosidase inhibitory activity. Issue 31 (3rd August 2017) - Buck, Matthew L.; Evans, Daniel M.; Evans, Victoria A.; Herkt, Dominik; Sharp, Hazel; Hollinshead, Jackie; Mitschang, Fabian; Murphy, Patrick J.; Nash, Robert J.; Wenbourne, Jack
Abstract: Tiruchanduramine1 was prepared using a convergent strategy with the longest linear sequence being eight steps. Synthetic1, displayed a broader range of inhibition than reported previously and, in addition to α-glucosidases, 1 also inhibits almond β-glucosidase, β-galactosidase and β- N -acetylglucosaminidase from jack bean. Graphical abstract: The alkaloid tiruchanduramine1 was prepared in racemic form from 3-aminopropan-1-ol and tryptophan using a convergent strategy with the longest linear sequence being eight steps.